Viabilidade energética da tecnologia gás natural adsorvido em carbonos ativados - Peixoto, Hugo Rocha (2020)
Natural gas, economically more attractive and cleaner than other fossil fuels, has been an important alternative to expanding the global energy supply. However, it has low energy density, which means storage and transportation costs are high. Adsorbed natural gas (ANG) is an option for vehicular application and can be stored at moderate pressures (~3.5–6.5 MPa). Finding the adsorbent material and storage conditions that insert this alternative in a scenario comparable to compressed natural gas is fundamental for the development of this technology. To save experimental effort, a mathematical model capable of reproducing or predicting successive charge/discharge cycles during the operation of an ANG tank from adsorption equilibrium data obtained by molecular simulation is being proposed in this study. The model, based on the Ideal Adsorbed Solution Theory (IAST) and implemented using gPROMS, is validated by experimental data from tanks filled with activated carbons available in the literature. It is possible to relate the performance of carbonaceous materials to their structures to predict the optimal pore size for ANG application that maximizes power supply and minimizes bed deactivation due to heavy alkane accumulation. Aiming to reduce storage tank deactivation, a pilot-scale process is adopted through simulations on Aspen Adsorption using a Pressure Swing Adsorption (PSA) technology to remove heavy hydrocarbons from natural gas with industrial active carbons. Each column operates according to four steps: pressurization, adsorption at 40 bar, depressurization and purge at 1 bar. The operating conditions of the process (flowrates, bed geometry and step times) are optimized, seeking the maximization of the performance parameters: purity, recovery and productivity, being possible to produce virtually C3+ free fuel, ideal for storage by adsorption. The influence of natural gas composition on the energy performance of GNA technology is analyzed.